Differences in the volume of sunflower honey produced in 2015 based on the different types of beehives and queen bee’s age - Takács, Marianna; Oláh, János (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
Nowadays more and more problems are caused by extreme weather conditions for the beekeepers society: both in the honey production and in the developments of the colonies in spring. This year’s acaci aseason is characterized by a cool and rainy weather and the ground frost caused damage. At the time of the other main bee pasture carring the weather was favorable. The aim of the current research was to compare the volume of the sunflower honey of Nagy-Boczonádi lying hives and the loarder-type hives. The study included families where the queen bee’s age was different. Five Nagy-Boczonádi lying hives (two-family) and 10 loarder-type hives were included in the study. The age of the queen bees was distinguished on the basis of the current year queens marker color. In 2015 the queens marker color was blue. In the case of families in Nagy-Boczonádi lying hives the vintage of queen bees: 2012, 2013, 2014 and 2015. In the loarder-type hives the vintage of queen bees: 2013, 2014 and 2015. We compared the pre-carry total weight of hives to after-carrying total weight of hives to follow up the quantity of sunflower honey. In case of loarder-type hives reached over the limit of 20 kg per family is, however, a case of lying hives 17 kg was the maximum. The beekeeping is located in Nyírmada in Szabolcs-Szatmár-Bereg county, and accessible from the main road No. 41. The beekeeping uses two kind of bee pastures: sunflowers and acacia. During the acacia season the beekeeping is staying in place, but during the sunflower season should wander every year. In 2015 investigated colonies there were in Jász-Nagykun-Szolnok county, Tiszaörs outskirts of town were 200 ha sunflower field. Our results of practical respect we can say that in case of the performance of loarder-type hive’s colonies exceeded the performance of lying hive’s colonies.